Pattern and prevalence of substance abuse in Kashmiri population: a review - Yaqoob, Arjimand; Ashraf, Sharika (International Journal of Advances in Medicine, 2022)
Substance abuse is rampant in modern world including Kashmir valley. It has become one of the major health concerns of the society. Here we present review of various studies about prevalence and effects of drug abuse in Kashmir valley. Different electronic databases PubMed, Science Direct and Google Scholar, for last 20 years were searched for articles describing drug abuse in Kashmir valley. Out of 10 results, 4 were reviewed published from 2012to 2021. In Kashmir, the consumption of opioids has increased significantly with heroin injection not being uncommon. Youth are more vulnerable to the menace which destroys the productive years of their life. Many factors like conflict 2012 to 2021 zone, peer pressure, unemployment, vulnerable to this menace, educational stress is responsible for the substance abuse among individuals. Drug abuse threatens the social fabric of our community. It causes enormous suffering to not only the individual caught in this abuse but also his whole family. To overcome this menace multipronged approach is required with interventions at family and, community level, various government agencies, NGO’s and most important by medical specialists.